EFFECT OF RESIDUAL-GAS ON CU FILM DEPOSITION BY PARTIALLY-IONIZED BEAM - KOH, SK; JIN, ZG; LEE, JY; JUNG, HJ; KIM, KH; CHOI, DJ (A V S AMER INST PHYSICS, 1995)
Cu films were deposited on Si(100) substrate by partially ionized beam in a pressure of 10(-6) Torr. Ion beam current densities were measured with and without Cu evaporation, respectively, in order to evaluate an effect of residual gas on the Cu deposition process. The ion beam current density measured without Cu evaporation, which is mainly due to ionized residual gas, was linearly increased with acceleration voltage, and the dependence of the ion beam current density on vacuum pressure was significantly decreased with 10(-5)-10(-7) Torr. Total ion beam current density measured during Cu deposition, effects of ionized Cu particles and residual gas, was increased with acceleration voltage, and the magnitude of the total ion beam current density is nearly the same as the ion beam current density due to ionized residual gas. Growth rate and preferred orientation were increased with acceleration voltage, and grain size of the deposited films was in a range of 1000 Angstrom, which was not dependent on acceleration voltage. Root-mean-square roughness of deposited films was reduced from 138 to 18 Angstrom with a change in acceleration voltage from 0 to 3 kV. These changes of the film's features could be attributed to the bombardment effect of ionized residual gas. (C) 1995 American Vacuum Society.
Keywords: THIN SILVER FILMS; ION-BOMBARDMENT; ELECTRICAL-PROPERTIES; GROWTH; MICROSTRUCTURE